Tooth Saving Solutions- Best Transport Media for Avulsed Tooth? A Review - Prasada, L Krishna; C, Priya; K, Ramya M (Journal of Biomedical and Pharmaceutical Research, 2024)
Avulsion is considered one of the most serious types of trauma to teeth as it can displace the tooth from its bone socket and also causes injury to its surrounding structures. The neurovascular supply is greatly hampered by the complexity of this damage, which typically leads to pulp vitality loss. The treatment for avulsed tooth is immediate replantation but, in several situations, it is not possible. The maintenance of viability of PDL cells on the root surface of avulsed tooth is absolutely necessary till the tooth is placed back in the socket to prevent ankylosis and replacement resorption.Research has led to the development of various transport media for avulsed teeth that can produce conditions that closely resembles the environment of alveolar socket with adequate osmolality, pH, nutrition & metabolites.This review sheds light on various transport media used for avulsed teeth, its ideal requirements and newer research on such solutions.Keywords: Transport media, Avulsion, Avulsed tooth